(3GdMQcGJ GdfSGFjI GdYeGdjI hShb GdYed (B:s (3GdfRYI GdQGOjcGdjI aj JMOjGJ GdWHbI GdHhQLhGRjI hfhY GdLfS (B/s - (3YhV, GdSjO Mfais ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2010)
(3jVe GdThGgO GdJGQjNjI, GdeTcdGJ GdLJeGYjI heWGdH Shb GdYed, bhi GdYeGdI GdfSGFjI hShb GdYed, CSGdjH GdgjefI Ydi GdYeGdI GdfSGFjI, gLQI GdYeGdI GdfSGFjI hGdYhdeI, fhY GdLfS hYde GdGLJeGY GdfShjs
(3GdeQGLY U(B.263s
Keywords: (3GdMQcGJ GdYeGdjIs; (3GdYeGd GdfSGAs; (3Gdbhi GdYGedI(B- (3GdfSGAs